Financial Mechanism for the Development of Islamic Business in the Russian Federation - H.A. Youssef (Модернизация, инновация, развитие, 2021)
Purpose: in modern conditions in Russia there are regions with a large proportion of the Muslim population that implement initiatives for the development of Islamic business, however, the functioning Islamic business model practically does not differ from the traditional model of Russian entrepreneurship, only individual elements and principles, types and forms of entrepreneurial activity based on principles of Sharia, Islamic banking is being promoted more actively. In this regard, the purpose of this article is to study the financial mechanism for the development of Islamic business in the Russian Federation in the context of the implementation of key areas of state support for entrepreneurship at the federal and regional levels.Methods: the study is based on the use of general scientific methods of induction and deduction, a review of scientific sources; the quantitative assessment is based on the calculation of statistical indicators, in particular: the relative size of the structure of segments of the Islamic economy with comparative studies in the country context of the volume of the halal food market, chain and basic indicators of the series of dynamics of directions of state support for Islamic business and regional levels.Results: the article analyzes the main directions, tools and institutions for the implementation of state support for Islamic entrepreneurship in foreign practices, indicating the active development of legislative, regulatory and organizational infrastructure, large-scale financing of infrastructure support programs. The article also provides an analytical overview of the development of Islamic business in the Russian Federation. Particular attention in the article is paid to the analysis of federal and regional programs to support Islamic entrepreneurship, which made it possible to identify the features of the implementation of the mechanism of state support.Conclusions and Relevance: it has been determined that in Russia the most developed segments of Islamic entrepreneurship are the halal industry, the development of which is supported by state programs at the sub-federal level, and the relationship of partner banking. The factors that limit the development of Islamic entrepreneurship in the Russian Federation have been identified: inadequacy of federal programs for financing Islamic business; the local nature of support for Islamic entrepreneurs within the framework of regional programs («point» principle).